Increased risk for radiographic osteoarthritis features in young active athletes: a cross-sectional matched case–control study. Issue 2 (February 2015) - Roemer, F.W.; Jarraya, M.; Niu, J.; Silva, J.-R.; Frobell, R.; Guermazi, A.
Summary: Objective: Prevalence data on radiographic osteoarthritis (ROA) in young active athletes is sparse. Aim was to assess in a matched case–control design the frequency of ROA in an athlete population and whether athlete status, gender, previous anterior cruciate ligament (ACL) surgery and age increase the odds for ROA. Design: 135 consecutive athletes (82% soccer players) 18–36 years old and 550 non-athletes aged-matched controls had knee radiography (Lyon-Schuss protocol) for assessment of subacute or chronic knee complaints. Patients with acute trauma or fractures were excluded. Radiographs were graded according to the Kellgren–Lawrence and OARSI grading schemes. In addition, medial and lateral intercondylar notch osteophytes were scored. We used logistic regression model to assess the association of ROA and specific radiographic OA features with athlete status, prior ACL surgery, gender and age, adjusting for each other. Results: 19.4% of patients were 18–22 years old, 26.4% were 23–27, 22.6% were 28–32, and 31.5% were 33–36 years old. 18.7% were female and 8.8% had previous ACL surgery. 8.5% had ROA and 6.0% had evidence of JSN. The adjusted odds ratios (aOR) for ROA were 2.8 (95% confidence interval 1.4, 5.5) for athletes, 7.0 (3.5, 13.9) for previous ACL surgery and 3.3 (1.2, 9.0) for age range 32–36. Athlete status significantly increased odds for tibiofemoral osteophytes [aOR 2.9 (1.6, 5.4)] and comparably for notch osteophytes [aOR 2.3 (1.1, 4.7)]. Conclusions: Athlete status, higher age and previous ACL surgery increase the risk of ROA with surgery being the strongest risk factor.